IMPLEMENTASI PERENCANAAN PEMBANGUNAN PARTISIPATIF MELALUI MUSRENBANGDES SEBAGAI PERWUJUDAN DEMOKRATISASI DI TINGKAT DESA - Kamaruddin, K; Kamal, Afina Aurellya; Adekayanti, Putri Kusma (Pusat Riset dan Publikasi, 2024)
This study aims to know the implementation of participatory development plan at the Village development plan deliberation, in Lape village Lape Sub-District in 2023. The type of this study was qualitative study. Sources of data in this study were primary and secondary data. The numbers of informants in this study were 11 informants consisted of Head village of Lape, Village Secretary of Lape Village, head of Village Consultative Board of Lape Village and Lape Village Communities. The methods used to collect data were through observation, interviews, and documentation. Data analysis in this study was carried out using Miles and Huberman's qualitative data analysis techniques which consist of data collection, data reduction, data presentation, and drawing conclusions. The results of this study showed that communities’ involvement in the development process in Lape Village was quite good so that the developments that had planned by apparatus of Lape Village have been done in accordance with the needs of the Lape Village communities. Therefore the success of a participatory development cannot be separated from the participation of the communities where communities’ participation were the most important and most important factor in the development and implementation process so that a successful development plan can be realized in Lape Village.